THE EFFECT OF NATURAL FEED REPLACEMENT ON GROWTH AND SURVIVAL RATE OF DOKUN LARVAE (Barbodes lateristriga) - M Imam Choiri; Nuraini Nuraini; Netty Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research was conduct d on December 2019 until January 2020 in Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Riau University, Pekanbaru. The purpose of this research is to know the effect of feed replacement that are appropriate for growth and survival rate of Dokun larvae (Barbodes lateristriga). The method used in this research was an experimental method with Completely Randomized Design (CRD) one factor with five treatments and three replications, The treatment apllied in this study were C10A30 = Chlorella sp for 10 days + Artemia sp for 30 days. C20A20 = Chlorella sp. 20 days + Artemia sp 20 days.C10K30 = Chlorella sp 10 days+Dapnia sp 30 days. C20K20 = Chlorella sp 20 days + Dapnia sp 20 days. C10A10K10T10 = Chlorella sp 10 days + Artemia sp. 10 days + Daphnia sp 10 days + Tubifex sp 10 days. The results showed that the best treatment in P5 = (Chlorella sp 10 days + Artemia sp. 10 days + Daphnia sp 10 days + Tubifex sp 10 days) the absolute weight growth of 0,130 g, the absolute length growth of 1,12 cm, and a specific growth rate of 11, 60%, and survival rate was 66,7%, Water quality during the study, the temperature range was 26-27oC, pH range was between 6-7 and DO was 5.2-6.7. Keyword :Chlorella sp., Artemia sp., Daphnia sp., Tubifex sp., Growth, (Barbodes lateristriga)